Community Empowerment through the Batik Industry: The Facilitative Role of the Urban Village Administration in Strengthening the Creative Economic Capacity of Residents in Kampung Batik Okra Surabaya - Rasidi Rasidi; Dandy Wirawan; Zainal Fatah (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
Kampung Batik Okra, located in Kranggan Urban Village, Bubutan District, Surabaya City, represents a community-based creative economy initiative officially inaugurated on 28 December 2022 by the Surabaya City Government. This study aims to analyze the facilitating role of the urban village administration in strengthening the creative economic capacity of residents through the batik industry, as well as to identify supporting and inhibiting factors for community empowerment in Kampung Batik Okra. A descriptive qualitative approach was employed, with data collected through in-depth interviews, participatory observation, and document analysis. Informants were purposively selected, encompassing village government officials, batik group administrators, artisans, and academic facilitators. The findings reveal that the urban village administration performs three principal facilitative roles: (1) facilitation of training and skill enhancement; (2) facilitation of market access and promotion; and (3) facilitation of multi-stakeholder partnerships. These roles contribute significantly to the strengthening of residents’ creative economic capacity, as evidenced by an increase in active artisans, product diversification, and expanded marketing networks. Nevertheless, limited human resource capacity within the village administration, inconsistent community participation, and restricted access to capital remain structural barriers requiring more systemic policy interventions. This research offers a conceptual framework of empowerment-based facilitating roles for urban villages, which may serve as a reference for developing creative economy villages in Indonesian urban areas.